Implementasi Teknik Penilaian pada Anak Usia Dini di TK Khalifah Baciro Yogyakarta - Wahyuni, Arisna (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2019)
This study aims to determine the description of the implementation of the assessment conducted at the Khalifah Baciro Kindergarten. This research uses descriptive qualitative method. Data collection techniques are by interview, documentation and observation. The subjects of the study were the Principal and Kindergarten Teacher Khalifah Baciro. The results of the study that in the Khalifah Baciro Kindergarten had carried out the assessment process, where the assessment process was carried out through five stages, namely, planning, implementation or recording, processing of learning outcomes, archiving and reporting, in the assessment in the Khalifah Baciro Kindergarten conducted with three stages, namely daily report , midlle semester and semester report cards. In providing an assessment to children, a child development report every semester has been provided directly by the management or foundation, namely a daily learning assessment, a recapitulation of children's development values and a midterm development report. Besides laopran per semester, at the Khalifah Kindergarten also conducts an assessment in the middle of the semester or commonlycalled the middle semester